Analisis Kepuasan Pengguna Aplikasi Maxim di Kota Cilegon Menggunakan Integrasi EUCS, IPA, dan TRIZ - Akbar Gunawan; Atia Sonda; Yohana Hasianna Manullang; Ade Sri Mariawati; Aditya Rahadian Fachrur; Dhena Ria Barleany (Journal Industrial Manufacturing, 2026)
This study aims to analyze user satisfaction of the Maxim application in Cilegon City and formulate service improvement priorities through the integration of End-User Computing Satisfaction (EUCS), Importance Performance Analysis (IPA), and TRIZ methods. The main problem of this study stems from user complaints about the Maxim application, specifically related to address point accuracy, map display readability, and application response speed. The study uses a quantitative approach with a survey method by distributing questionnaires to 96 active Maxim application users in Cilegon City. The research attributes are arranged based on five EUCS dimensions, namely content, accuracy, format, ease of use, and timeliness. The data obtained are tested for validity and reliability, then analyzed using IPA to measure the level of conformity, the gap between expectations and performance, and priority attributes for improvement. Furthermore, the TRIZ method is used to formulate innovative solutions to attributes in the top priority quadrant. The results show that the average performance value of the Maxim application is 3.445, while the average user expectation value is 3.831, resulting in a gap value of -0.385. The average suitability level of 89.9% indicates that the Maxim application's performance has not fully met user expectations. The attributes that are the main priority for improvement are address point accuracy, ease of understanding the map display, and application response speed. Based on the TRIZ analysis, the innovative principles obtained are intermediary and parameter changes. Recommendations for improvement include updating GPS-based locations, adding a "nearest building" feature, using more varied colors on map components, and storing frequently used pick-up and drop-off points on the user's device. This study shows that the integration of EUCS, IPA, and TRIZ can be used as a systematic approach to evaluate user satisfaction while generating recommendations for improving online transportation applications. Keywords: Maxim, user satisfaction, EUCS, IPA, TRIZ, online transportation